2022
DOI: 10.34172/jpe.2022.26166
|View full text |Cite
|
Sign up to set email alerts
|

Determining the factors associated with the pattern and severity of coronary artery involvement in patients with acute coronary syndrome

Abstract: Introduction: Acute coronary artery syndrome is a term to describe a wide range of diseases associated with a sudden and severe decrease in blood flow to the heart. Objectives: This study aimed to evaluate the variables related to the severity and type of coronary artery involvement in patients with the acute coronary syndrome (ACS). Patients and Methods: This study is a retrospective analytical descriptive study. The statistical population of this study included patients who were admitted to the vascular ward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…As our study showed, the incidence of MACE was higher in the group with less SBP, and the results of their study were in line with ours. In addition, another study showed the correlation between coronary artery disease severities based on gender, age, number of vessels involved, family history, blood pressure, and diabetes ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…As our study showed, the incidence of MACE was higher in the group with less SBP, and the results of their study were in line with ours. In addition, another study showed the correlation between coronary artery disease severities based on gender, age, number of vessels involved, family history, blood pressure, and diabetes ( 25 ).…”
Section: Discussionmentioning
confidence: 99%